2021
DOI: 10.1002/jbm.b.34951
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrated human amniotic membrane regulates tenocyte expression and angiogenesis in vitro: Implications for a therapeutic treatment of tendinopathy

Abstract: Tendon injuries are among the most common ailments of the musculoskeletal system.Prolonged inflammation and persistent vasculature are common complications associated with poor healing. Damaged tendon, replaced with scar tissue, never completely regains the native structural or biomechanical properties. This study evaluated the effects of micronized dehydrated human amnion/chorion membrane (μdHACM) on the inflammatory environment and hypervascularity associated with tendinopathy. Stimulation of human tenocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Although excessive inflammation is thought to impair healing, recent evidence suggests that placental-derived products can interact with tenocytes and reduce the inflammatory response to support tendon healing [ 30 , 34 ]. This study sought to evaluate the effect of placental CTMs on tenocyte inflammatory gene expression (i.e., CXCL8 , TNF , TGFβ1 , TGFβ3 , and MMP1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although excessive inflammation is thought to impair healing, recent evidence suggests that placental-derived products can interact with tenocytes and reduce the inflammatory response to support tendon healing [ 30 , 34 ]. This study sought to evaluate the effect of placental CTMs on tenocyte inflammatory gene expression (i.e., CXCL8 , TNF , TGFβ1 , TGFβ3 , and MMP1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that the regulatory proteins contained within micronized dehydrated human amnion-chorion membrane (dHACM) reduce the expression of inflammatory genes, proteases, and ECM components, and decrease the presence of active MMPs and type III collagen [ 34 ]. The findings of the current report align with the previous report by Moreno and colleagues [ 34 ] but also suggest that the decellularization of placental tissue may promote better regulation of inflammatory processes by human tenocytes. Although decellularization is performed to reduce the host inflammatory response, it can also affect the structures and entities within the ECM, disrupting its functional characteristics [ 1 , 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…μdHACM treatment was found to reverse the pro-inflammatory-induced increase in type 3 collagen expression and decrease the IL1β-induced type 1 and type 3 collagen levels. Researchers have also found that μdHACM can promote angiogenesis [ 99 ]. The decellularized biological scaffold can also be an effective alternative for future tendon ligament injuries after ensuring mechanical properties and avoiding rejection in vivo [ 100 ].…”
Section: Products Of Tendon and Ligament Reconstruction And Repairmentioning
confidence: 99%
“…[10][11][12][13][14] However, the mechanical properties, particularly the tensile property of the hAMs used in surgeries, are insufficient, severely restricting the promotion and application of hAMs. [15][16][17][18] Hydrogel is a material that contains a large amount of water in an internal three-dimensional network, and it has similar physical and biological properties to the extracellular matrix, making it an ideal bioadhesive material for various tissues. [19][20][21][22][23][24][25][26] Hydrogels' superior adhesion, biocompatibility, degradation, and antibacterial properties have led to rapid advancements in the eld of bioadhesion in recent years.…”
Section: Introductionmentioning
confidence: 99%